👤

Ofer 25 de puncte :) [tex] \sqrt{x+ \sqrt{2x-1}} + \sqrt{x- \sqrt{2x-1} } = \sqrt{2} [/tex]

Răspuns :

[tex] \sqrt{x+\sqrt{2x-1} }+ \sqrt{x-\sqrt{2x-1} }= \sqrt{2} [/tex]|²
[tex]x+ \sqrt{2x-1}+2 \sqrt{x+ \sqrt{2x-1}} \sqrt{x- \sqrt{2x-1} }+x- \sqrt{2x-1}= 2[/tex]

[tex] 2x+2\sqrt{(x+ \sqrt{2x-1} )(x- \sqrt{2x}-1 )} =2[/tex]
[tex] 2x+2 \sqrt{ x^{2} -x \sqrt{2x-1} + x\sqrt{2x-1}-(2x-1)} =2[/tex]
[tex]2x+2 \sqrt{ x^{2} +1-2x}=2<=>2x+2 \sqrt{ (x-1)^{2}}=2<=>2x+2(x-1)=2<=>2x-2+2x[/tex]=2
<=>4x=2=>x=2


  se ridica la patrat toata relatia si se obtine:
x+[tex] \sqrt{2x-1} [/tex]+2[tex] \sqrt{x+ \sqrt{2x-1} } \sqrt{x- \sqrt{2x-1} } [/tex]+x-[tex] \sqrt{2x-1} [/tex]=2
2x+2[tex] \sqrt{(x+ \sqrt{2x-1)}(x- \sqrt{2x-1}) } } [/tex]=2
2x+2[tex] \sqrt{ x^{2} -2x+1} [/tex]=2
2x+2[tex] \sqrt{(x-1)^2} [/tex]=2
2x+2(x-1)=2
2x+2x-2=2
4x=4
x=1